Efeito de dietas com fontes lipídicas e glicogênicas no período de transição de Primíparas leiteiras sobre: perfil metabólico, produção de leite e reprodução - Maria Alexandra Torres Artunduaga (2009)
Increasing the availability of glucogenic and lipogenic nutrients during the transition period has been hypothesized to improve energy balance and to decrease the incidence and severity of metabolic and reproductive disorders in early lactation. Therefore, the objectives of this study were to compare the effects of a glucogenic or a lipogenic diet on blood metabolites, metabolic hormones, follicular dynamics and milk production and composition in primiparous dairy cows during the transition period. Cows (n= 40) were fed on a standard diet from wk 3 prepartum to wk 6 postpartum. Cows received either a lipogenic or glucogenic supplement during the transition period and were randomly assigned to 1 of 4 treatments as follows: control, calcium salts of soybean fatty acids - Megalac-E (100g prepartum and 250g postpartum), toasted soybean (400g prepartum and 800g postpartum) and propylene glycol (300 ml pre and postpartum). Diets were isocaloric (net energy basis). Blood samples were taken from each animal 10 and 5 days prior to the expected calving date and at days 7, 14, 21, 28, 35 and 42 postpartum. Ultrasound scanning was performed in all cows on Monday, Wednesday and Friday. Dominant follicle diameter and luteal volume tissue was determined for each cow. Follicles were classified according to diameter in classes I, II, III and IV. Interval from parturition to first post partum ovulation was determined. Milk production was recorded on days 10, 20, 30 and 40 postpartum and milk composition was determined on the same days. Milk yield did not differ among treatments (P=0.067). Yield of 3.5% fat corrected milk (FCM 3.5%) was higher for cows supplemented with Megalac-E and propylene glycol (P = 0,047) compared to other treatments. Milk protein and fat did not differ among treatments. Milk lactose content was higher for the propylene glycol treatment (P<0.05) when compared to other treatments. Insulin and glucose concentrations were significantly higher in the Megalac-E treatment (P<0.05). The lowest insulin and glucose concentrations were observed on cows supplemented with propylene glycol. Non esterified fatty acid concentration (NEFA) were lower for all treatments compared to control group (P<0.05). Plasma IGF-I concentration was higher for treatments receiving the lipogenic supplements (P<0.05). The best pattern of follicular classification was observed for the Megalac-E treatment. This particular group also showed the lowest interval from parturition to first post partum ovulation. (P<0.05). Overall, results suggest that calcium salts of soybean fatty acids reduced the dramatic metabolic and endocrine changes characteristic of the transition period, reflecting in improved energy balance which could be associated with better reproductive and productive performance.